‘Eviction & Compensation’, the Village of al-Samara, 1948-1951: Israel and the Baha’i Community Relations - Rosen, Shai (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2014)
Baha'i settlement in Israel and the Bahei community's relations with local authorities is understudied to-date. The article follows Israel's takeover of ‘Baha’i lands in a-Samara, a village in the Jordan Valley, after the independence war.Unlike Arab owned lands, Israel preferred to purchase the Baha'i lands of al-Samara at full cost and compensate some of the tenant farmers living of them, since the Baha'i community did not take part in the national struggles and held a neural position in the 1948 war. Nonetheless, Israel acted decisively against villagers who refused eviction in return to financial reimbursement. The article further examines the differences between Israeli policy towards, Baha'i land owners and the Arab tenant farmers, within the demilitarized territories on the Syrian border.